Addressing the Surgical Deficit: A Global Imperative for Plastic and Reconstructive Surgeons - Rachel W. Davis, MD; Walter D. Johnson, MD, MPH, MBA, FACS, FAANS; Larry H. Hollier, Jr., MD, FACS (Plastic and Reconstructive Surgery, Global Open, 2019)
Summary:. Despite poor access to quality surgical and anesthesia care for the majority of the world’s people, with greatest impact on low- and middle-income countries, surgery has only recently begun to gain acceptance as a necessary component of global health. As a leader in global surgical funding, the field of Plastic and Reconstructive Surgery is uniquely positioned to influence change in global policy and financial support. For improvements in surgical access and outcomes worldwide, investment in surgical systems, commitment to national surgery, obstetric, and anesthesia planning, and continued evaluation and improvement of care delivery should be pursued.